1984
DOI: 10.1007/bf00410731
|View full text |Cite
|
Sign up to set email alerts
|

Changes in properties of phytopathogenic bacteria effected by plasmid pRD1

Abstract: Transfer of plasmid pRD1 from Escherichia coli K 12J62 -1 to phytopathogenic bacteria, Agrobacterium tumefaciens, Xanthomonas beticola and Erwinia carotovora subsp. carotovora caused changes in conjugant properties not determined by the plasmid and the emergence of the properties not present in the parent strains. Clones have been obtained with intermediate properties between donor and recipient, including those with altered or lost virulence. In transconjugants of A. tumefaciens virulence increased. In transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The loss of pathogenic phenotype has been reported upon the transfer of pRD1 from E. coli to E. carotovora [23]. The transconjugants of E. carotovora obtained in the present study showed no such loss of pathogenicity and retained the ability to cause maceration of potato tuber tissue, thus indicating that Inc-P plasmids do not affect the pathogenic phenotype of E. carotovora.…”
Section: Carotovorasupporting
confidence: 53%
“…The loss of pathogenic phenotype has been reported upon the transfer of pRD1 from E. coli to E. carotovora [23]. The transconjugants of E. carotovora obtained in the present study showed no such loss of pathogenicity and retained the ability to cause maceration of potato tuber tissue, thus indicating that Inc-P plasmids do not affect the pathogenic phenotype of E. carotovora.…”
Section: Carotovorasupporting
confidence: 53%
“…The presence of pectic substrates in the soil and the diminished gene/protein production resulting from the deletion of the pectate lyase gene may have contributed to the significantly lower survival of the genetically engineered strain in the loam soil. Such alterations in cell physiology and biochemistry have been reported with E. carotovora transconjugants [24]. With respect to the variable survival pattern of the GEM in the loam soil, Scanferlato and colleagues [15] show a similar variable recovery pattern of a genetically engineered Erwinia strain using MPN analysis.…”
Section: Discussionmentioning
confidence: 66%
“…The presence of pectic substrates in the soil and the diminished gene/protein production resulting from the deletion of the pectate lyase gene may have contributed 0 2 5 10 15 20 25 30 67 72 85 74 85 103 102 99 9 10 8 7 1 26 11 32 81 84 87 78 103 100 89 117 13 13 25 17 25 18 17 21 to the significantly lower survival of the genetically engineered strain in the loam soil. Such alterations in cell physiology and biochemistry have been reported with E. carotovora transconjugants [24]. With respect to the variable survival pattern of the GEM in the loam soil, Scanferlato and colleagues [15] show a similar variable recovery pattern of a genetically engineered Erwinia strain using MPN analysis.…”
Section: Discussionmentioning
confidence: 67%